The Newton wars and the beginning of the French Enlightenment - Shank, John Bennett (University of Chicago Press, 2008)
A study of public culture, this book digs beneath the surface of the commonplace narratives that link Newton with the Enlightenment to examine the actual historical changes that brought them togather in 18th century time and space. Shank re-examines Newton's status as the father of modern physics and the philosophe movement.